Development of New Ni-Al Porous Alloys for Metal-Supported Solid Oxide Fuel Cells; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Kirdyashkin A. I. Aleksandr Ivanovich; Kitler V. D.; Maznoy A. S. Anatoly Sergeevich; Soloviev A. A. Andrey Aleksandrovich; Kovalchuk A. N. Anastasia Nikolaevna; Ionov I. V. Igor Vyacheslavovich (Advanced Materials and Nanotechnology, 2014)
Title screen